1995
DOI: 10.1002/hep.1840220525
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin and interleukin-1 related hepatic inflammatory response promotes liver failure after partial hepatectomy

Abstract: Impairment of various functions of the liver and concomitantly increased levels of parameters of liver damage, a clinical entity termed liver failure, is commonly seen after partial hepatectomy. We investigated in a rat model whether damage of the remnant liver was due to local inflammatory responses, and related to endotoxin or interleukin-1 (IL-1). To address this question, the effects of partial hepatectomy on infiltration of immunocompetent cells and expression of major histocompatibility complex (MHC) cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 30 publications
1
38
0
3
Order By: Relevance
“…It was, however, increased after PCS, as it was in the ligated lobes after PBL in our study (Stärkel et al, 2001) and in other studies (Uemura et al, 2000). It has been demonstrated that administration of exogenous recombinant IL-1␤ in vivo diminishes the replicating surge of hepatocyte DNA synthesis after PH (Boulton et al, 1997), whereas blocking its effect by administration of IL-1␤ receptor antagonists during the first 24 hours after PH enhances hepatocyte proliferation in rats (Boermeester et al, 1995). This cytokine might exert a negative growth modulator effect preventing uncontrolled hepatocyte proliferation (Higashitsuji et al, 1995).…”
Section: Laurent Et Alsupporting
confidence: 48%
“…It was, however, increased after PCS, as it was in the ligated lobes after PBL in our study (Stärkel et al, 2001) and in other studies (Uemura et al, 2000). It has been demonstrated that administration of exogenous recombinant IL-1␤ in vivo diminishes the replicating surge of hepatocyte DNA synthesis after PH (Boulton et al, 1997), whereas blocking its effect by administration of IL-1␤ receptor antagonists during the first 24 hours after PH enhances hepatocyte proliferation in rats (Boermeester et al, 1995). This cytokine might exert a negative growth modulator effect preventing uncontrolled hepatocyte proliferation (Higashitsuji et al, 1995).…”
Section: Laurent Et Alsupporting
confidence: 48%
“…41 cytokine. While this study was in progress, Boermeester et al showed that hepatocyte proliferation was enhanced in rats As discussed below, this is a potential mechanism by which nonparenchymal cell generation of IL-1 might be initiated given IL-1ra during the first 24 hours after partial hepatectomy, 45 an observation that would be predicted from the after hepatectomy in vivo, but these observations also raise the possibility that the in vitro findings we described were inhibitory role that we postulate for IL-1 in the events following partial hepatectomy. an artifact caused by cell manipulation.…”
Section: 33mentioning
confidence: 82%
“…After major liver resection, the hepatic mononuclear phagocytic system, the body's main clearing mechanism for endotoxin, is reduced, [13][14][15][16] allowing spillover of gut-derived bacteria and endotoxin into the systemic circulation. 17,18 Indeed, endotoxin was demonstrated in plasma from patients undergoing a hemihepatectomy, whereas in plasma from patients undergoing other major abdominal surgery, endotoxin was not detectable. 19 Endotoxin can induce an enhanced expression of leukocyte and endothelial adhesion molecules and is a potent stimulator of the PMN oxidative burst in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%